In vitroactivity of tedizolid and comparator agents against Gram‐positive pathogens responsible for bone and joint infections. Issue 10 (October 2017) - Ract, Pauline; Piau‐Couapel, Caroline; Compain, Fabrice; Auzou, Michel; Michon, Jocelyn; Cattoir, Vincent
Abstract : Abstract : Tedizolid, a second‐generation oxazolidinone that displays a potent activity against Gram‐positive pathogens, could be an interesting option for the treatment of bone and joint infections (BJIs). The aim of the study was to determine minimal inhibitory concentration (MIC) of tedizolid against a collection of 359 clinical isolates involved in clinically‐documented BJIs and to compare them to those of comparator agents used in Gram‐positive infections. Of the 104 Staphylococcus aureus and 102 coagulase‐negative staphylococci (CoNS) isolates, 99 and 92% were categorized as susceptible to tedizolid, respectively (MIC25 =0.12/0.25 μg ml ‐1 and MIC90 =0.25/0.5 μg ml ‐1 ), regardless of their methicillin resistance. MIC50 and MIC90 for the 51 enterococci, the 50 Corynebacterium spp. and the 52 Propionibacterium spp. were either equal or inferior to 0.5 μg ml ‐1 . Altogether, tedizolid possessed a potent in vitro activity against most of the BJI Gram‐positive pathogens with 95% of them exhibiting a MIC ≤0.5 μg ml ‐1 .